Analytical approach to estimating the influence of rock fragmentation on the clean concrete-rock shear behavior - Xiaolin Zhao; Svetlana Melentijevic; Yupeng Shen; Zenkui Sun; Kaiyuan Wang; Zhiqiang Li; Jincui Xu (Case Studies in Construction Materials)
The pile side friction (PSF) of rock-socketed piles (RSPs) is a frictional response closely related to the shear mechanism of the pile-rock interface (PRI), as well as the state of the rock. In order to study the PSF of RSPs, the PRI is first idealized as a regular triangular asperity. Then, the development process of the PSF is described through a shear model of concrete-regular triangular rock (CRTR), which is under the condition of constant normal stiffness (CNS). Next, using the Weibull distribution and the statistics theory, an evolutionary equation of the rock fragmented variable (RFV) is established to describe the fragmented state of the rock. Based on the shear model of the CRTR and the evolutionary equation of RFV, a shear model of concrete-regular triangular fragmented rock (CRTFR) is constructed to characterize the variation of the shear stress-shear displacement curve (τ-s curve). Finally, the calculated results of the shear model of the CRTFR are compared with the experimental results to verify the accuracy of the model. The results show that the calculation results of the established CRTFR shear model are in good agreement with the experimental results, and can accurately describe the variation characteristics of the linear stage, pre-peak softening stage, post-peak softening stage and residual stage of the τ-s curve. The model parameters have clear physical meanings, and their mathematical expressions can be obtained through theoretical derivation. Parameter sensitivity analysis shows that the initial normal stress, normal stiffness, asperity angle, basic friction angle, residual friction angle and rock crushing parameters have a significant effect on the shear response of the concrete-rock interface (CRI).